Inherited Metabolic Diseases: A Clinical Approach - Hoffmann, Georg F.; Nyhan, William L.; Zschocke, Johannes (Springer-Verlag Berlin Heidelberg, 2010)
The explosion of insights in the field of metabolic disease has shed light on diagnostic as well as treatment options. This book presents an overview of the major groups of metabolic disorders. It presents clinical and diagnostic details with a system and symptom based to facilitate an efficient diagnostic work-up of individual patients
Description based upon print version of record
Keywords: Aufsatzsammlung; Erbkrankheit; Stoffwechselkrankheit